A PC-based driving simulator using virtual reality technology - Kang, Hooi Siang; Abdul Jalil, Mohamad Kasim; Mailah, Musa (ACM, 2004)
Driving simulators are frequently used for vehicle system development, human factor study, and vehicle safety research by enabling the reproduction of the actual driving environments in a safe and tightly controlled environment. Recent development of powerful desktop computer workstations can now support the computational requirement of small to medium-scale driving simulators. The driving simulator for this research is developed using PC-based workstations that are capable of producing high fidelity graphics at reasonable cost. The VR-based simulator gives a driver on board the impression that he drives an actual vehicle by predicting vehicle motion caused by the driver input and feeding back the corresponding visual, motion, audio and proprioceptive cues to the driver. This research is intended to provide a test bed for simulating driving related task using virtual reality technology.